Prognostic Role of c-Jun Activation in Patients with Areca Quid Chewing-related Oral Squamous Cell Carcinomas in Taiwan - Ru-Cheng Kuo (Journal of the Formosan Medical Association, 2006)
Overexpression or activation of c-Jun has been implicated in the pathogenesis of several types of cancer. Treatment of oral cells with areca nut extract in culture can increase c-Jun proto-oncogene mRNA levels. The purpose of this study was to investigate the possible role of c-Jun activation in the pathogenesis and prognosis of areca quid chewing-related oral cancer in Taiwan. Methods: We immunohistochemically examined c-Jun protein activation in human oral squamous cell carcinomas (SCC) using an anti-phosphospecific c-Jun (pc-Jun) antibody on paraffin-embedded sections. Results: Positive pc-Jun staining was observed in 42 of 70 (60%) cases of oral SCC. No significant correlation was found between pc-Jun expression and patients' age, gender, oral habit, cancer location, clinical stage, tumor size and lymph node status. Kaplan-Meier curves showed that oral SCC patients with positive pc-Jun staining or positive lymph node metastasis had significantly shorter overall survival (p < 0.018 and 0.001, respectively, by log-rank test). Conclusion: These results indicate that c-Jun activation may play an important role in the carcinogenesis of oral SCC. Positive pc-Jun staining may serve as an adjuvant marker of worse prognosis in patients with oral SCC in Taiwan.